Cattle grazing and fish recovery on US federal lands: can social–ecological systems science help?. (16th January 2018) - Charnley, Susan; Gosnell, Hannah; Wendel, Kendra L; Rowland, Mary M; Wisdom, Michael J
Abstract : In the western US, grazing management on federal lands containing habitat for fish species listed under the US Endangered Species Act (ESA) has sparked social conflict and litigation for decades. To date, the problem has been addressed through a top‐down environmental governance system, but rangeland managers and grazing permittees now believe there is a need for more innovative management strategies. This article explores how social–ecological systems (SES) science can address rangeland management challenges associated with the survival and recovery of ESA‐listed fish species on federal lands where cattle grazing is a dominant type of land use. We focus on the Blue Mountains of eastern Oregon, where the Mountain Social Ecological Observatory Network's Blue Mountains Working Group is collaborating with diverse stakeholders to develop and test a novel grazing system designed to reduce the impact of cattle on riparian areas using an SES science approach. Although not a complete solution, SES science holds promise for improving rangeland management.